Reproduction de l'huître creuse (Crassostra gigas) dans le Bassin de Marennes Oléron. La pêche expérimentale de larves d'huîtres, indicateurs de ponte et de recrutuement. Analyse spatio-temporelle et relation avec l'environnement - Soletchnik, Patrick (2000)
This study is based on catched larvae data base produced since C. gigas was first imported into the Charentais Sounds (late 1960s, early 1970s). The method for catching larvae using a towed net remained unchanged between 1950 and 1998. Four sites have been sampled in the Bay since 1970, two situated in the Seudre estuary and two in the middle of the Bay. Two other sites from near the mouth of the Charente River have been sampled since 1982. For each sample, oyster larvae were counted in four size classes, from the young larva (1-4 days) to near metamorphosis (16-20 days). Each year, 100 to 150 captures were carried out at all sample sites between June and September. Captures from July and August represent 99% of the total. The main variables were: capture frequency, start of the spawning season (PP), date of first spawning peak (DP), spawning index and recruitment index (IR)2. From a descriptive point of view, the spawning season may begin in late June or only during the first two weeks of August. It lasts 2 to 8 weeks with one to four major spawning peaks. Thus, the "classification" of the spawning season in C. gigas, as observed through larvae capture, shows high interannual variability. Cette étude s'appuie sur les données de captures de larves d'huîtres, réalisées depuis son importation dans les pertuis Charentais (fin des années 60, début des années 70). La méthode de pêche de larves au "filet tracté est restée la même entre 1950 et 1998. Chaque année, 100 à 150 pêches sont effectuées sur l'ensemble des sites de prélèvement, entre juin et septembre. Les pêches de juillet – août représentent 99% des captures. Les principales variables sont : la fréquence de capture, le début de la saison de ponte (PP), la date d'apparition du premier pic de ponte (PP), l'indice de ponte (IP) et l'indice de recrutement (IR). D'un point de vue descriptif, la saison de ponte peut débuter fin juin ou seulement au cours de la première quinzaine d'août. Elle dure 2 à 8 semaines avec 1 à 4 pics majeurs de ponte. Ainsi, la ...